THE EFFECT OF CONSUMPTION OF PORK (SUS BARBATUS) ON BLOOD PRESSURE, HEMOGLOBIN LEVEL AND TOTAL CHOLESTEROL LEVEL - Supriati Wila Djami; Meirina Loaloka (Jurnal Riset Kesehatan, 2022)
Pork is a very difficult meat to digest because it contains a lot of fat and pork causes many diseases, namely hardening of the arteries, increased blood pressure, excruciating chest pain (angina pectoris) and inflammation of the joints and if pork is consumed it can affect the organs in the body. This study aims to determine the effect of pork consumption on blood pressure, hemoglobin levels and total cholesterol levels. This research was conducted on people who often consume pork in Baun village, Amarasi Barat sub-district, with as many as 51 respondents consisting of 20 males and 31 females. Based on the results of the study, it is known that people who often consume pork 3 to 4 times a month have hemoglobin levels within normal limits with a percentage of 66.67%, blood pressure tends to be high with a percentage of 47.06% and high total cholesterol levels with a percentage of 53%. So it can be conclude that consuming pork can increase cholesterol levels in the body blood.